2004
DOI: 10.1097/01.blo.0000129346.29945.3b
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intercellular Communication through Gap Junctions May Contribute to Progression of Osteoarthritis

Abstract: Our aim was to support the hypothesis of a specific association between gap junctions in synovial tissue and the presence of osteoarthritis, as evidenced by differences between osteoarthritis and non-osteoarthritis synovia in the number of gap junctions, the amount of gap-junction protein, and the amount of enzymatic activity produced through a pathway mediated by gap-junction intercellular communication. An average of 4.41 gap junctions were found per 100 cells counted in the osteoarthritis synovia, compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Cell-to-cell coupling through gap junctions support the formation of complex cellular networks that favor the intercellular exchange of nutrients and second messengers (D’Andrea, Calabrese et al 1998). Gap junctions are present in the synovium (Kolomytkin, Marino et al 2000), and have been shown to affect increased production of matrix metalloproteinases by FLS subjected to pro-inflammatory cytokines (Kolomytkin, Marino et al 2002, Marino, Waddell et al 2004) as well as constitutively in clinical OA samples (Marino, Waddell et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Cell-to-cell coupling through gap junctions support the formation of complex cellular networks that favor the intercellular exchange of nutrients and second messengers (D’Andrea, Calabrese et al 1998). Gap junctions are present in the synovium (Kolomytkin, Marino et al 2000), and have been shown to affect increased production of matrix metalloproteinases by FLS subjected to pro-inflammatory cytokines (Kolomytkin, Marino et al 2002, Marino, Waddell et al 2004) as well as constitutively in clinical OA samples (Marino, Waddell et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…30 Several studies have implicated Cx43 in the etiology of OA. 19,25,49,50 Synovial biopsies from patients with OA were shown to have an increase in Cx43 expression and an increase in the size and number of gap junction plaques. 25 Ex vivo analysis of these cells revealed that pharmacological inhibition of Cx43 function could reduce the basal and IL-1β-stimulated production of collagenase activity.…”
Section: Introductionmentioning
confidence: 99%
“…19,25,49,50 Synovial biopsies from patients with OA were shown to have an increase in Cx43 expression and an increase in the size and number of gap junction plaques. 25 Ex vivo analysis of these cells revealed that pharmacological inhibition of Cx43 function could reduce the basal and IL-1β-stimulated production of collagenase activity. 19,25 Additionally, the inflammatory cytokine IL-1β has been shown to increase the expression of Cx43 in articular chondrocytes 49,50 and synovial fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synovial cells are connected to each other by an extensive networks of gap junctions, and it may mediate some cellular processes [12,13]. Kolomytkin Marino et al reported that increased ICJP may contribute to the progression of osteoarthritis [15]. The synovial lining cells from patients with osteoarthritis (OA) produced MMP constitutively and in response to stimulation by IL-1β.…”
Section: Discussionmentioning
confidence: 99%